PERILAKU PETANI DALAM MENGHADAPI RISIKO PRODUKSI CABAI MERAH (Capsicum annuum L.) DI KECAMATAN CISAYONG - Rahmawantie, Salsabila; Djuliansah, Dedi; Tedjaningsih, Tenten (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Red chili is one of horticultural commodities that has high economic value, so it is widely cultivated by farmers. In the cultivation process, farmers often face risks and uncertainties. Production risk is one of the risks that must be faced by red chili farmers in the cultivation process. The high or low level of production risk will affect the behavior of farmers in carrying out the cultivation process. The purpose of this study was to analyze the level of red chili production risk, analyze the influence of red chili production factors, and analyze farmers' behavior in facing red chili production risk. This research was conducted in Cisayong which is one of the red chili commodity centers in Tasikmalaya Regency by taking a sample of 37 red chili farmers using the stratified random sampling method. The analysis method used was production risk analysis using coefficient of variation, production factor analysis using Cobb-douglas production function, and analysis of farmers' behavior in facing risk using the Moscardi and de Janvry risk aversion model. The results showed that (1) Production risk of red chili in Cisayong was fairly high with a coefficient of variation (CV) value of 0.57. (2) Factors that simultaneously affect red chili production are land area, seed, fertilizer, insecticide, fungicide, lime, and labor (3) The behavior of red chili farmers in Cisayong was classified as risk-averse in facing risks.